PERBANDINGAN EFEKTIFITAS PROMOSI KESEHATAN DENGAN METODE MEDIA AUDIO VISUAL (VIDEO) DAN LEAFLET TERHADAP TINGKAT PENGETAHUAN IBU TENTANG MANAJEMEN DEMAM PADA BAYI DAN BALITA - Nurul " Amalliya; Yufitriana " Amir; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Medical personnel must achieve the target of MDG's 2015 to improve the health of infants and toddlers. One effort of improving the health of infants and toddlers is to increase mothers' knowledge with health promotion that depend on media. The purpose of this study was to known comparison of the effectiveness of health promotion with audio visual media (video) and leaflet for the level of mothers' knowledge about the management of fever in infants and toddlers. This study was quasy experiment with pretest and posttest design with two comparison treatments that obtained before and after being given health promotion with audio-visual media (video) and leaflet in the Working Area of Puskesmas Simpang Tiga Pekanbaru. The sample were 30 people who are taken by purposive sampling techniques. The instruments were questionnaires that have been tested for validity and reliability. The analysis can be used univariate and bivariate analysis using a paired t-test and unpaired t test. The results showed an increase significantly the level of mothers' knowledge about the management of fever in infants and toddlers in the experimental group with the audio-visual media (video) after given health promotion on the management of fever in infants and toddlers with p value ( 0.000) <α (0.05). It means that health promotion effective to improve the mother's knowledge about management of fever in infants and toddlers with audio-visual media, so the knowledge increase. This results are expected to be input and information about the implementation of the audio-visual media (video) and leaflet. Keywords: Audio visual, health promotion, infants, knowledge, management of fever,toddlers